Safety of ezetimibe in lipid-lowering treatment: systematic review and meta-analysis of randomised controlled trials and cohort studies - Ling Li; Jing Li; Yang Wang; Bert Aertgeerts; Gordon Guyatt; Per Olav Vandvik; Qiukui Hao; Heyue Du; Na Su; Haoming Tian; Sheyu Li; Safi U Khan; et al. (BMJ Medicine)
Objective To determine the harms of ezetimibe in people who need lipid-lowering treatment.Design Systematic review and meta-analysis.Data sources Randomised controlled trials and cohort studies.Eligibility criteria for selecting studies Studies comparing ezetimibe with placebo, standard care, or other lipid-lowering agents in people who need lipid-lowering treatment with a follow-up duration of at least six months (or 24 weeks). The relative effects for potential harms of ezetimibe were pooled by use of random effect pairwise meta-analyses for randomised controlled trials and the evidence from observational studies was narratively summarised. The certainty of evidence was assessed using the Grading of Recommendation Assessment, Development, and Evaluation.Results 48 randomised controlled trials with 28 444 participants (median follow-up 34 weeks, range 24-312 weeks) and four observational studies with 1667 participants (median follow-up 282 weeks, range 72-400 weeks) were included. The meta-analyses of randomised trials showed moderate to high certainty that ezetimibe was not associated with cancer (relative risk 1.01; 95% confidence interval 0.92 to 1.11), fractures (0.90; 0.74 to 1.10), discontinuation due to any adverse event (0.87; 0.74 to 1.03), gastrointestinal adverse events leading to discontinuation (1.34; 0.58 to 3.08), myalgia or muscular pain leading to discontinuation (0.82; 0.51 to 1.33), neurocognitive events (1.48; 0.58 to 3.81), or new-onset diabetes (0.88; 0.61 to 1.28). The narrative analysis of observational studies provided consistent findings. No credible subgroup effects were identified for the harm outcomes, including shorter versus longer follow-up duration of trials.Conclusions Ezetimibe results in little to no difference in adverse events or other undesirable effects compared with placebo, usual care or other lipid-lowering agents.Review registration PROSPERO CRD42020187437.